The Social Support effect in the construction of resilience weaving among firefighters Comparative clinical study of four cases Central unit Bordj Bou Arreridj town - Zerroug, mounira (Journal of Social Sciences and Humanities, 2021)
The individuals practicing in the intervention groups are witness inhuman situation and various violent events , that the victims experience each time , given the nature of their activity includes the dangers important as well on physical level because of the risks of this work , as at the level psychological even the impact of the trauma following their contact with the victims . However there are individuals in this category who return to work without being really affected by the trauma this indicated a capacity of resilience . The question that arises , What are the factors favoring resilience ? ..And for that I concentrated my research by choosing social support as a factor favoring the development of resilience in this category .I also chose the clinical method and his tools like the interview and the observation. ,I also chose four cases out of thirty-four cases from the main unit of the state of Bordj Bou Arreridj and i compared between them, the first tow cases accessed resilience from the social support they received .However the last tow cases where unable to establish resilience due to dysfunction of their family environment which previously provided them with support . Following this study it is recognized that the social support is an important factor in the development of resilience in this category . In conclusion of my cases study it appeared that the repeated confrontation with the trauma in the professional field dose not consist an element participating in development of resilience